The role of legumes in protein sovereignty in Europe and Africa - issues, differences and complementarities - (:unkn) unknown (My University, 2025)
Protein autonomy is essential for food sovereignty at a time when Europe and Africa are in chronic deficit.In addition to production, legumes provide other services to help solve issues such as the closing of the nitrogen cycle, tensions on the protein market, human nutrition and its impact on health, and pest control without the use of synthetic pesticides. Seed legumes as well as soybean and groundnut, are a source of protein and fibre to balance the human diet and combat obesity (Europe) or undernutrition (Africa). Forage and seed legumes are excellent protein sources for rations for livestock, either ruminants or monogastric animals. All these legumes provide environmental services in rotations or in co-culture with nonleguminous crops. In particular, they can help to reduce the use of synthetic nitrogen fertilisers in Europe and enrich soils with nitrogen in Africa, as well as extending crop rotations to combat weeds and diseases.These aspects, to be applied in Europe as much as in Africa, will enable us to combine production with respect for the environment. Lastly, value chains that generate income and employment can be created or enriched thanks to legumes initially on a local scale and then on a wider scale. Nevertheless, the current lack of knowledge about these species and their uses remains significant, requiring national and international investment.
Keywords: African Research